Current Issues of Inbound Tourism in the Republic of Kazakhstan and Ways of Promotion - AYETOV, Sayat; URUZBAYEVA, Nazym (Journal of Environmental Management and Tourism; Vol 9 No 6 (2018): JEMT Volume IX Issue 6(30) Fall 2018DO - 10.14505//jemt.v9.6(30).09, 2019)
This article analyzes the current state of inbound tourism in the Republic of Kazakhstan, the authors carried out a sociological analysis that identified the main problems hampering the development of inbound tourism in Kazakhstan and proposed the solution of infrastructure problems through the establishment of a lending institution.